C‐reactive protein assessment to predict early septic complications after laparoscopic bowel resection for endometriosis: a diagnostic study. (5th June 2019) - Scattarelli, A; Carriou, M; Boulet, L; Chati, R; Coget, J; Bridoux, V; Tuech, J‐J; Roman, H
Abstract : Objective: To assess the predictive value of C‐reactive protein (CRP) level for early septic complications after laparoscopic bowel resection for endometriosis. Design: Retrospective study using data prospectively recorded in the CIRENDO database. Setting: University tertiary referral centre. Population: Three hundred and three women managed by segmental resection or disc excision for colorectal endometriosis in 40 consecutive months. Methods: C‐reactive protein was routinely measured at postoperative days 4, 5, and 6. Bowel fistula, pelvic abscess, and pelvic infected haematoma were prospectively recorded. Main outcome measures: A receiver operating characteristic (ROC) curve was built to assess the best cut off CRP value to predict early septic complications. Results: The incidence of bowel fistula and pelvic abscess/infected hematoma were 2 and 7.9%, respectively. The CRP cut‐off value of 100 mg/l at postoperative day 4 predicts early septic pelvic complications (sensitivity, specificity, positive and negative predictive values of, respectively, 76, 83, 30.2, and 90.4%), and the area under the curve was 0.85 (95% CI 0.78–0.92). Conclusion: Postoperative CRP monitoring is useful in the prediction of early septic pelvic complications following bowel endometriosis surgery, with possible impact on the management of postoperative outcomes and hospitalisation stay. Tweetable abstract: Levels of CRP ≥100 mg/l at day 4 after bowel resection or excision for endometriosis are associated with early septic pelvic complications. Abstract : Tweetable abstract Levels of CRP ≥100 mg/l at day 4 after bowel resection or excision for endometriosis are associated with early septic pelvic complications.